Assessment of maize-legume intercropping as a way for sustainable intensification in mixed farming systems for smallholder farmers in Jimma, Ethiopia - Yatogo, Hinase (International Maize and Wheat Improvement Center, 2024)
Ethiopia is one of the targeted countries in the SI-MFS project to represent highland MFS in East and Southern Africa. The agriculture sector is a source of livelihood for more than 80% of the population and contributes 45% to the GDP in Ethiopia, showing the importance of agriculture in the country (Dendir & Simane, 2019). Similar to other developing countries, MFS, especially animal production, plays an important role in supporting the livelihood of the population as Ethiopia has the largest livestock population (Worqlul et al., 2022). Crop production in Ethiopia is cereal-dominated (Belachew et al., 2022). Most crops are cultivated in the rainy season, from mid-June to mid-September, as almost all grain production by smallholders is rainfed (Belachew et al., 2022; World Bank Climate Change Knowledge Portal, 2021). The main calorie requirements are provided by maize (Zea Mays), teff (Eragrostis tef), sorghum (Sorghum bicolor L. Moench), wheat (Triticumaestivum L.), and barley (Hordeum vulgare) among cereals, and enset (Ensete ventricosum) provides the most among roots and tubers in the Ethiopian diet (Abate et al., 2015).